Mental CO2 emissions from energy use in Iran and implications for future - Ali Azimi, Naser (Opción, 2019)
This paper aims to identify the factors that have influenced the change of CO2 emissions related to energy use at both aggregated and sectorial levels in the Iranian economy via the Logarithmic Mean Division Index (LMDI) method. The results show that per capita GDP, energy intensity and the fossil fuel intensity of energy are the three dominant contributors to changes in CO2 emissions at the aggregated level. As a conclusion, attention must be paid to the composition of fossil fuels and the share of fossil fuels in energy consumption in order to achieve a decrease in CO2 emission.